How Integrating Aboriginal Perspectives into the Classroom Affects Students Attitudes Towards Aboriginal People - Tiffany Prete (Journal of Contemporary Issues in Education, 2020)
This paper explores the methods employed by Alberta Education to teach Alberta students about the Indigenous Peoples of Canada. Currently, Alberta Education has two approaches, which are: 1) the integration of the First Nations, Metis, and Inuit Policy Framework (FNMI), which is a framework that is a means to educate all Albertans on the history of Aboriginal Peoples, and 2) an optional Aboriginal Studies coursework. An urban high school participated in this research study, which was under the call for the integration of the FNMI policy framework and also offered Aboriginal Studies 10. I used a Blackfoot theoretical framework, grounded in an Indigenous research methodology, alongside principles of the Beadworking paradigm to conduct the research. I employed a survey that was quantitative in nature to determine students’ attitudes towards the Indigenous Peoples of Canada. I was interested in identifying whether taking Aboriginal Studies 10 made a difference in the participants’ views of Indigenous Peoples. I used principal-component factor analysis and multivariate analysis of variance (MANOVA) to analyze the data. The results from the MANOVA analysis indicate that the Aboriginal Studies 10 class plays a role in students’ perceptions of Indigenous Peoples specifically. These results indicate that students who participated in the Aboriginal Studies 10 course had a more positive view of Indigenous Peoples than students who did not participate in Aboriginal Studies 10.